Навчання англійської мови професійного спрямування в умовах дистанційної освіти - Караєва, Тетяна В'ячеславівна; Караева, Татьяна Вячеславовна; Karaieva, Tetiana; Шевченко, Світлана Петрівна; Шевченко, Светлана Петровна; Shevchenko, Svitlana (My University, 2021)
UK: У статті розглянуто проблеми навчання англійської мови професійного спрямування в умовах дистанційної освіти. Висвітлено організаційно-педагогічні умови, прийоми та методи застосування дистанційного навчання у процесі викладання англійської мови професійного спрямування. Особливу увагу приділено особливостям навчання англійської для спеціальних цілей в умовах онлайн-режиму за методичними комплексами, розробленими для аудиторних занять. Наведено сучасні інформаційні технології, програмне забезпечення та їх інструментарій, призначені для освітніх цілей дистанційної освіти. На прикладі власного досвіду розглянуто можливу процедуру розроблення, організації та впровадження в навчальний процес програми навчання англійської мови професійного спрямування в умовах дистанційної освіти у процесі підготовки здобувачів закладу вищої освіти за напрямом підготовки «Аграрні науки та продовольство». RU: В статье рассмотрены проблемы обучения английскому языку профессионального направления в условиях дистанционного образования. Освещены организационно педагогические условия, приемы и методы применения дистанционного обучения в процессе преподавания английского языка профессионального направления. Особое внимание уделено особенностям обучения английскому языку для специальных целей в условиях онлайн-режима по методическим комплексам, разработанным для аудиторных занятий. Приведены современные информационные технологии, программное обеспечение и их инструментарий, предназначенные для образовательных целей дистанционного образования. На примере собственного опыта рассмотрена возможная процедура разработки, организации и внедрения в учебный процесс программы обучения английскому языку профессионального направления в условиях дистанционного образования в процессе подготовки соискателей высшего учебного заведения по направлению подготовки «Аграрные науки и продовольствие». EN: Making the leap from the face-to-face classroom to the online one may seem incredibly difficult, but in reality it is much easier than we could think. As educators we have already got skills, strategies, methodological approaches that we could bring into online classroom. Being experienced instructor of English it is clear how to involve students in learning process and how to motivate them even online. Everyone understands that good teaching is good whether it is done face-to-face or online. The authors of this article describe the tools, techniques, and activities for online teaching of ESP course (English for Specific Purposes) for the students of specialties “Agronomy” and “Horticulture and Viticulture”. There are thousands of English language courses, blogs, vlogs, and channels on social media sites now. There are many recommendations and ways how to read in English, watch videos, communicate with native speakers. More and more resources for online teaching are available now. Usually all these methodological materials are for General English. It is not easy to teach online ESP course without online methodological complex. The authors of the paper share their experience how to teach online with the textbooks for physical classroom. The ways how to develop all four skills (reading, listening, writing and speaking) with the help of online tools are described in the paper. There is no the only right way how to teach online. This kind of methodology is new. But it has already known that online teaching depends on the quality of the technologies the students and educators apply. It also depends on how experienced and confident the instructor is in online teaching. The authors of the article prove that the more we teach online, the more confident we feel and the quicker we will get at it. Teaching of ESP course online is reality and new horizons of methodology.
Обучение профессиональному английскому языку в условиях дистанционного образования
Esp learning in the conditions of distance education
Keywords: дистанційне навчання; онлайн-режим; англійська мова професійного спрямування; особливості викладання; програмне забезпечення; дистанционное обучение; онлайн-режим; английский язык профессионального направления; особенности обучения; программное обеспечение; online teaching; ESP course; face-to-face classroom; physical classroom; online classroom